RENCANA JALUR INTERPRETASI LANSKAP PESISIR SEBAGAI DESA WISATA DI DESA PURWODADI, KABUPATEN MALANG - Debora Budiyono; Nuraini Nuraini; Alfiyah Alfiyah (BUANA SAINS, 2021)
Indonesia geographically has potential for coastal landscapes that could develop as coastal tourism. One of the potential coastal landscapes, located in Purwodadi Village, Tirtoyudo District, Malang Regency, East Java Province. Purwodadi Village has the potential for natural and cultural tourism objects that developed into a tourist village and had expected to improve the community's economy and maintain the quality of the village environment. The focus of the research was to create an interpretation of the coastal tourism landscape as a tourist village in Purwodadi Village. The method has used quantitative description while the analysis consists of path physical analysis, social analysis, object interpretation, visual analysis, tourist analysis, and social analysis. The results showed Purwodadi Village which has four routes, namely the main route, the residential route, the hill route, and the sea route. The model uses the tourist route plan in Purwodadi Village was interpreted into 4 tour packages, namely 1-day tour package, 3-day tour package, 5-day tour package, and 7 days or 1-week tour package